(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2024)
The student nurses were primary movers to their future nursing profession but often faced academic setbacks. These setbacks affect their development as future competent healthcare professionals due to the lack of consensus. This study uncovered the lived experiences of nursing students with their academic setbacks. A qualitative descriptive design was utilized, specifically Husserlian phenomenology and purposive sampling. The study was conducted at Union Christian College with 8 participants from February to March 2023. Data gathering procedures comprised of field notes, observations, and unstructured interviews with consideration of the ethical principles. Thematic Analysis was applied. It revealed four themes: (1) Battling Life Challenges explored the academic challenges of the nursing students that shaped how they managed the consequences, where problems, challenges, and negativities pound the students. Failures and challenges may either make them stronger or lead them to failure. (2) Adapting to Circumstances presented the adaptive strategies such as decision-making, coping mechanisms, stress-relieving methods, the law of attraction, anticipating the future, and motivations that strengthened students to continue pursuing their course. The motivations and adaptations made by the students during their darkest and lowest times became their stepping stones to achieving and conquering higher heights. (3) Reshaping the Broken Pieces showed the new learnings, discoveries, and optimism students have acquired necessary for their growth and progress. They were broken, trampled, and disintegrated, which made them find and connect all the jigsaw pieces of their life’s puzzle. (4) Refining for a Better Self is where realizations, feelings of fulfillment, and self-worth are made, just like a sword’s refining process during forging. They were forged, tempered, and folded, like the Excalibur sword, where they were strengthened by blood, sweat, and tears. It illustrates how students can transform and become stronger through their experiences, setbacks, and responses to adversities, much like a sword is forged and refined to become a better version of itself. It emphasized the importance of resilience, adaptability, and self-improvement in facing life’s difficulties. After going through all the stages and processes, they are worthy like a blade that has been sharpened and refined. Students once chose their future by acting upon what they needed to do and working out in their present times. They can either accept the challenge, remove the stuck sword from the stone, or leave it there. Various reasons and challenges either hindered or promoted the efficacy and efficiency of nursing students in their academic endeavors. As they encounter setbacks, the students need the vital role and support coming from their place, environment, and the academe/ institution that they were in. The study recommended that the institution provide better support for students with setbacks. A remotivation program for nursing students who experienced/experiencing academic setbacks should be implemented to promote emotional support and develop optimism in learning to prevent another setback. The findings of this study might be used to develop a support framework to guide them as they continue to pursue the course. Hence, further research must be done to explore a broader scope of nursing students’ experiences with academic setbacks to formulate a better conceptual framework to solve these problems in the nursing academe and institution.